Prevalence and risk factors for shedding of Cryptosporidium spp. oocysts in dairy calves of Buenos Aires Province, Argentina - Garro, Carlos Javier (2016)
In order to determine the prevalence and risk factors for shedding of Cryptosporidium spp. in dairy calves, a cross-sectional study was carried out in the northeastern region of Buenos Aires Province, Argentina. Fecal samples from a total of 552 calves from 27 dairy herds were collected, along with a questionnaire about management factors. Cryptosporidium spp. oocysts were detected by light microscopy using Kinyoun staining. Putative risk factors were tested for association using generalized linear mixed models (GLMMs). Oocyst shedding calves were found in 67% (CI95% = 49–84) of herds (corresponding to a true herd prevalence of 98%) and 16% (CI95% = 13–19) of calves (corresponding to a true calve prevalence of 8%). Withinherd prevalence ranged from 0 to 60%, with a median of 8%. Cryptosporidium spp. excretion was not associated with the type of liquid diet, gender, time the calf stayed with the dam after birth, use of antibiotics, blood presence in feces, and calving season. However, important highly significant risk factors of oocyst shedding of calves was an age of less or equal than 20 days (OR = 7.4; 95% CI95% = 3–16; P b 0.0001) and occurrence of diarrhea (OR = 5.5; 95% CI95% = 2–11; P b 0.0001). The observed association with young age strongly suggests an early exposure of neonatal calves to Cryptosporidium spp. oocysts in maternity pens and/ or an age-related susceptibility. Association with diarrhea suggests that Cryptosporidium spp. is an important enteropathogen primarily responsible for the cause of the observed diarrheal syndrome. Results demonstrate that Cryptosporidium spp. infection is widespread in the study region. Monitoring and control of this parasitic protozoan infection in dairy herds is recommended.